2005
DOI: 10.1177/00224669050390030101
|View full text |Cite
|
Sign up to set email alerts
|

Unproven Links

Abstract: The high degree of overlap of race and poverty in our society has led to the presumption in both research and practice that ethnic disproportionality in special education is in large measure an artifact of the effects of poverty. This article explores relationships among race, poverty, and special education identification to arrive at a more precise estimate of the contribution of poverty to racial disparities. District-level data for all 295 school corporations in a midwestern state were analyzed for this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(52 citation statements)
references
References 27 publications
3
46
1
2
Order By: Relevance
“…This is because, to date, the extant educational research has largely reported that minority children are more likely to be identified as having disabilities. This has led to characterizations of special education as “discriminatory” (Skiba et al, 2005, p. 142), maintaining “a new legalized form of structural segregation and racism” (Blanchett, 2006, p. 25), and constituting “institutionalized racism” (Codrington & Fairchild, 2102, p. 6). Yet, and despite these characterizations, our analyses of a longitudinal sample of U.S. schoolchildren followed from kindergarten entry to the end of middle school failed to yield any evidence of minority over-representation in special education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because, to date, the extant educational research has largely reported that minority children are more likely to be identified as having disabilities. This has led to characterizations of special education as “discriminatory” (Skiba et al, 2005, p. 142), maintaining “a new legalized form of structural segregation and racism” (Blanchett, 2006, p. 25), and constituting “institutionalized racism” (Codrington & Fairchild, 2102, p. 6). Yet, and despite these characterizations, our analyses of a longitudinal sample of U.S. schoolchildren followed from kindergarten entry to the end of middle school failed to yield any evidence of minority over-representation in special education.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of child-, family-, and school-level factors that might confound estimates of minority children's risk of disability identification include being born at very low birthweight (Grunau, Whitfield, & Davis, 2002), being raised in poverty (Blackburn, Spencer, & Read, 2013; Costello et al, 1996; Emerson, Einfeld, & Stancliffe, 2011), receiving lower quality (e.g., fewer language-based interactions) parenting and being raised in lower-resourced home environments (Altarac & Saroha, 2007; Costello et al, 1996), experiencing multiple risk factors (Myers & Pianta, 2008; Shaw, Owens, Giovannelli, & Winslow, 2001), and the state of residence (Wiley & Siperstein, 2011). Most of the extant studies have either not adjusted for these potentially confounding factors or have done so using school- or district-level averages (e.g., Oswald et al, 1999; Skiba et al, 2005; Sullivan, 2011; Talbott, Fleming, Karabotsos, & Dobria, 2011), thereby introducing substantial measurement error into the resulting directional estimates (Harwell & LeBeau, 2010). …”
Section: Extant Empirical Work's Methodological and Substantive Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…Racial disproportionality cannot be attributed to demographic factors, SES, single-parent households, family income, or to the hypothesized differential behavior of some racial and ethnic groups (Skiba, Poloni-Staudinger, Simmons, Feggins-Aziz, & Chung, 2005 ;. Research on classroom processes has determined that the problem of disproportionality begins with the teacher in the classroom, where the teacher's expectations and beliefs clash with the culture of some ethnic minority students.…”
Section: Ethnic Differences In Externalizing Behaviorsmentioning
confidence: 99%
“…higher rates of segregation from peers without disabilities (Blanchett, 2010; U.S. Department of Education, Office of Special Education and Rehabilitative Services, & Office of Special Education Programs, 2015). Education policy, the U.S. justice system, and a large body of research treat the ''overrepresentation'' of students of color in special education as likely evidence of bias and inappropriate identification of students of color (Donovan & Cross, 2002;Losen & Welner, 2001;Oswald, Coutinho, Best, & Nguyen, 2001;Skiba, Poloni-Staudinger, Simmons, Feggins-Azziz, & Choong-Geun, 2005). Yet some new research challenges previous conclusions of racial bias by examining the relation between race and disability in light of confounders (e.g., socioeconomic status) and by better accounting for the nested nature of students within school contexts MacMillan & Reschly, 1998;Morgan et al, 2015;Shifrer, 2018;Shifrer, Muller, & Callahan, 2011).…”
mentioning
confidence: 99%